(NoSNOWNYE STRUKTURY SOWREMENNOJ ALGEBRY (B/s - (NbAHTURIN(B, (N`RIJ aLEKSANDROWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1990)
(NbIBLIOGR(B.: (NS(B. 307-309s
(NuKAZ(B. (NOBOZNA^ENIJ(B, (NPREDM(B.: (NS(B. 310-318s
Keywords: (NaLGEBRA WYS[AQs